Kondisi Biofisik Serta Gangguan Terhadap Hutan Pada Areal Buffer Zone Bantaran Sungai Apo Distrik Jayapura Utara - Valentin Paisei; Soetjipto Moeljono; Rima H.S. Siburian (Cassowary, 2021)
APO river has a length of 3 kilometers with a width of 7 meters and flows from headwaters in the village Angkasa Pura to empty into the sea which is administered into the village administration area Bhayangkara. The purpose of this study to (1) identify the biophysical conditions in the area of the buffer zone of the river sepantaran Apo. (2) Identifying the form of land use in the bufferzone area of the Apo River from downstream to upstream. (3) Provide management recommendations in the form of land suitability directions to carry out Forest and Land Rehabilitation activities in the bufferzone area of the Apo river. Descriptive method with map interpretation and consists of several stages that include the preparation stage, the stage of processing and preliminary processing of data, field checking stage, the stage of data analysis, and recommendations on the implementation of Forest and Land Rehabilitation activities in the area of the river BufferZone Apo. Biophysical conditions of the area BufferZone river Apo has the characteristics of land cover types that include dry forest primary dry forest secondary, dryland farming mixed with shrubs, bushes, settlements, soil types litosol, with altitude ranging from 0 m asl - 690m above sea level . BufferZone slope in the area of very varied ranging from flat to very steep.In accordance with the decline in the quality of primary dryland forest to secondary dryland forest covering 22.04 hectares in 2009-2018 and activities that resulted in the removal of 44.80 hectares of secondary forest in 2000-2009, the large changes in the nature of both deforestation and degradation of from 2000 to 2018 thus covering an area of 66.84 hectares or 18.94% of the total research area, namely the Apo river bufferzone. Most of the areas that are categorized as quite suitable are forest areas that are experiencing deforestation and degradation and the recommended land is suitable enough to carry out RHL activities in the bufferzone area of the Apo River, only covering an area of 91.05 hectares or 25.80% of the bufferzone area. Apo river.